Rethinking EU Consumer Law - Howells, Geraint (Taylor & Francis, 2017)
In Rethinking EU Consumer Law, the authors analyse the development of EU consumer law on the basis of a number of clear themes, which are then traced through specific areas. Recurring themes include the artificiality of the EU's consumer image, the problems created by the drive towards maximum harmonisation, and the unexpected effects EU Consumer Law has had on national law. The book argues that EU Consumer Law has the potential of enhancing the protecting of consumers throughout the EU and could offer a model for consumer law elsewhere in the world, but in order to unlock this potential, there needs to be a rethink with regard to the EU's approach to consumer law and policy.